Economic Management of Income Earned by Cruise Ship Workers from Denpasar Municipality in Their Place of Origin - Manik Pratiwi, AA.; Diah Kusuma Dewi, Putu (Udayana Journal of Social Sciences and Humanities, 2017)
This study aims to identify the ways applied in the economic management of the income earned by cruise ship workers from Denpasar Municipality in their place of origin and to identify the benefits enjoyed by families of the cruise ship workers and their place of origin through the economic income management. This study examines the ways employed in the economic income management. This research took place in Denpasar Municipality of Bali Province. Samples were taken by the random sampling technique. The informants are cruise ship workers from Denpasar Municipality and their families. The thematic content analysis is applied in this study. The main findings of this study indicate that cruise ship workers have managed their income economically. They do so by investing their income to do a business, buy land, and build a boarding house. They also join Bali Seafarers Cooperative as a member. Their families enjoy many benefits with the economic income management by cruise ship workers.